Faith and Islam through the texts of the Holy Quran - Jameel, Abed H. (Humanities Journal of University of Zakho, 2013)
Through my research I got the following results : 1- Speakers differed in their definition of faith and they defined it in different ways, however, the correct view of Faith is that : it is the ratification of heart and approval the tongue and the work with essentials. 2-Theologians have spoken in the increase and decrease of faith, and it seems to me that faith can not increase in regard to ratification but in the acceptance is in the increase and decrease of good deeds , the more a person of his good deeds the more grows of faith and vice versa. 3-Islam is the absolute compliance of language, but in Sharia it is the obedience and compliance as stated by the Prophet (peace be upon him) Thus aware of religion necessarily. 4-As for the difference between faith and Islam, the most predominant correctness is that they have one sense, because the scholars said in their books the house of Islam and the house of war and did not said the house of faith, it seems that there is no difference between them .